Chhilka - Mahreen, Zuberi (book group Karachi, 2008)
Chhilka is an Urdu word that simply means "peel" or "skin". It refers to the outer covering of fruits, vegetables, or nuts. For example, the outer layer of a banana or an onion is its chhilka.